2005
DOI: 10.1002/jgm.732
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term expression of the human glucocerebrosidase gene in vivo after transplantation of bone‐marrow‐derived cells transformed with a lentivirus vector

Abstract: The recombinant lentiviral vector transduces HSCs that are capable of long-term gene expression in vivo. This approach is potentially useful for the treatment of patents with Gaucher disease and other lysosomal storage disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 56 publications
1
17
0
1
Order By: Relevance
“…Much progress has been made in the design of improved vectors including recombinant adeno-associated viral vectors [109] and HIV-1-based lentivirus vectors [110] that express human GC cDNA. Mice transplanted with lentivirus-transduced bone marrow-derived hematopoietic stem cells overexpressing human GC exhibited relatively high levels of GC activity in various tissues including bone marrow and spleen, but also the brain, 2-6 months after transplantation [111]. Although the suitability of the latter strategy to ameliorate Gaucher disease-associated symptoms in humans remains to be demonstrated, the results obtained in mice are encouraging.…”
Section: Other Therapeutic Strategies For Gaucher Diseasementioning
confidence: 99%
“…Much progress has been made in the design of improved vectors including recombinant adeno-associated viral vectors [109] and HIV-1-based lentivirus vectors [110] that express human GC cDNA. Mice transplanted with lentivirus-transduced bone marrow-derived hematopoietic stem cells overexpressing human GC exhibited relatively high levels of GC activity in various tissues including bone marrow and spleen, but also the brain, 2-6 months after transplantation [111]. Although the suitability of the latter strategy to ameliorate Gaucher disease-associated symptoms in humans remains to be demonstrated, the results obtained in mice are encouraging.…”
Section: Other Therapeutic Strategies For Gaucher Diseasementioning
confidence: 99%
“…Subsequent clinical studies showed that the transduction efficiency and engraftment of autologous stem cells from Gaucher patients occurred with insufficient efficiency for therapeutic efficacy [13]. More recently, adenoviral [14], lentiviral [15], and adeno-associated viral (AAV) vectors [16] harboring the human glucocerebrosidase (hGC) cDNA have also been evaluated, though none in a systemic animal model of Gaucher disease. Compared to other viral-based vectors, AAV vectors offer some advantages for the treatment of Gaucher disease [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Lentiviral vectors drive stable, long-term transgene expression in the brain [21][22][23] , transfect adult, mature neurons and possess a larger cloning capacity than adeno-associated viral vectors (AAV). Because of its many advantages, lentiviral vectors have been proposed for treating a wide range of disease such as hematopoietic disorders and CNS diseases [24][25][26] , and for cancer therapy by delivery of anti-endostatin and anti-angiostatin gene into target tumor endothelial cells, to kill tumor cells [27,28] .…”
Section: Discussionmentioning
confidence: 99%